World Economic Outlook, May 1997 : Globalization: Opportunities and Challenges. (World Economic Outlook; World Economic Outlook, 1997)
This paper presents an outlook for the world economy for 1997. The paper highlights that the world economic growth quickened during 1996 following widespread deceleration of activity in 1995. Economic and financial conditions are generally propitious for the global expansion to continue in 1997 and the medium term at rates at least matching those seen during the past three years. The paper underscores that in many countries, structural reforms are enhancing the role of market forces and thereby strengthening the basis for sustained, robust growth.